Phase I Trial to Evaluate the Tolerance, Pharmacokinetics and Efficacy of the Broad-Spectrum ErbB Family Inhibitor Larotinib Mesylate in Patients With Advanced Solid Tumors - Liu, Jingrui; Zhang, Hong; Zhu, Xiaoxue; Chen, Hong; Li, Xiaojiao; Ding, Yanhua (Frontiers in Pharmacology, 2021)
Background: The presented phase I, first-in-human study evaluated the tolerance, pharmacokinetics, and preliminary efficacy of larotinib mesylate in patients with advanced solid tumors. Methods: Cancer patients were assigned to receive larotinib mesylate at 50–400 mg dose levels until disease progression or intolerance. Dose-limiting toxicities were assessed during Cycles 0 and 1. Pharmacokinetic evaluations were performed after the first dose and at steady-state. Results: Twenty-five patients with solid tumors were enrolled in the dose-escalation study. No DLTs were observed. Acne-like rash (68.0%), diarrhea (48.0%), paronychia (48.0%), and anemia (48.0%) were the most reported treatment-related adverse events. No clear linear pharmacokinetic characteristic could be drawn, and obvious accumulation was observed. Two patients with non-small cell lung cancer experienced a partial response, and 15 patients had stable disease after treatment. Conclusion: Continuous oral administration of larotinib mesylate at 50–400 mg daily demonstrated a favorable safety profile, and anti-tumor activity was observed in patients with advanced solid tumors.